Photo release of nitrous oxide from the hyponitrite ion studied by infrared spectroscopy: evidence for the generation of a cobalt-N2O complex: experimental and DFT calculations - Chacón Villalba, María Elizabeth (2017)
The solid state photolysis of sodium, silver and thallium hyponitrite (M2N2O2, M = Na, Ag, Tl) salts and a binuclear complex of cobalt bridged by hyponitrite ([Co(NH3)5-N(O)-NO-Co(NH3)5]4+) were studied by irradiationwith visible and UV light in the electronic absorption region. The UV–visible spectra for free hyponitrite ion and binuclear complex of cobalt were interpreted in terms of Density Functional Theory calculations in order to explain photolysis behavior. The photolysis of each compound depends selectively on the irradiation wavelength. Irradiation with 340–460 nm light and with the 488 nm laser line generates photolysis only in silver and thallium hyponitrite salts, while 253.7 nm light photolyzed all the studied compounds. Infrared spectroscopy was used to followthe photolysis process and to identify the generated products. Remarkably, gaseous N2Owas detected after photolysis in the infrared spectra of sodium, silver, and thalliumhyponitrite KBr pellets. The spectra for [Co(NH3)5-N(O)-NO-Co(NH3)5]4+ suggest that one cobalt ion remains bonded toN2O from which the generation of a [(NH3)5CoNNO]+3 complex is inferred. Density Functional Theory (DFT) based calculations confirm the stability of this last complex and provide the theoretical data which are used in the interpretation of the electronic spectra of the hyponitrite ion and the cobalt binuclear complex and thus in the elucidation of their photolysis behavior. Carbonate ion is also detected after photolysis in all studied compounds, presumably due to the reaction of atmospheric CO2 with the microcrystal surface reaction products. Kinetic measurements for the photolysis of the binuclear complex suggest a first order law for the intensity decay of the hyponitrite IR bands and for the intensity increase in the N2O generation. Predicted and experimental data are in very good agreement.